2010
DOI: 10.1682/jrrd.2009.09.0146
|View full text |Cite
|
Sign up to set email alerts
|

Wheelchair axle position effect on start-up propulsion performance of persons with tetraplegia

Abstract: Abstract-This repeated measures study assessed the changes in speed, acceleration, stroke frequency, and shoulder range of motion (ROM) associated with different wheelchair axle positions in people with chronic cervical (C) 6 tetraplegia. Our main hypothesis is that the up and forward axle position is the most conducive to wheelchair propulsion, increasing speed and acceleration with a lower stroke frequency. In a chronic spinal cord injury (SCI) unit, we measured the speed, acceleration, stroke frequency, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Current clinical practice advocates for a forward axle position based on its advantage from a biomechanical perspective [34][35]. Pitch stability is rightly identified as an important consideration when determining how anterior the axle should be positioned.…”
Section: Discussionmentioning
confidence: 99%
“…Current clinical practice advocates for a forward axle position based on its advantage from a biomechanical perspective [34][35]. Pitch stability is rightly identified as an important consideration when determining how anterior the axle should be positioned.…”
Section: Discussionmentioning
confidence: 99%
“…However, in their study they did not find any difference between the two wheel positions with respect to mechanical efficiency, estimated exertion, breathlessness, seating comfort, estimated propulsion qualities, pelvic position or activity performance (Samuelsson et al 2004). Freixes et al (2010) also assessed the changes in speed, acceleration, stroke frequency and shoulder ROM in…”
Section: Subjectsmentioning
confidence: 94%
“…The axle position of down and backward axle position resulted in a lower speed and acceleration with a lower stroke frequency and an increased shoulder ROM. Freixes et al (2010) indicated that these were clinically important findings for wheelchair propulsion in their homes. The improvement of manual wheelchair propulsion has become increasingly important as the population of individuals using wheelchairs is growing and requires efficient mobility to maintain the user's independence and quality of life.…”
Section: Open Accessmentioning
confidence: 98%
“…Highly constraining tasks, such as startup or kerb mounting, can require up to three times more energy expenditure than propulsion [13]. However, in spite of its recurrence in daily life, few studies in the literature focused on propulsion and startup [14,15].…”
Section: Introductionmentioning
confidence: 99%